Financial Development and Income Inequality: Evidence from Latin America, 2001-2021 - Jung, Samuel; Zarate-Hoyos, German (Journal of Reviews on Global Economics, 2024)
Numerous studies delve into the theoretical frameworks on finance and inequality. However, there are too few empirical tests on its theoretical relations due to a lack of data to capture financial development. Additionally, due to the many social and economic dimensions of a large economy such as Brazil or Argentina, it is unrealistic to consider that labor market or political issues are the only culprits of income inequality. More research is needed to understand the dynamics of inequality. In this paper, we evaluate the influence of financial development on income inequality using nineteen countries in Latin America from 2001 to 2021. Two indicators of financial development are employed. First, I use the broader definition of money, M3, as a percentage of GDP to capture the liquid liabilities because M1 or M2 may be a poor proxy in economies with weak financial systems. Secondly, the ratio of credit to private sector to GDP is employed because financial intermediaries with higher volumes of credit are more involved in financial development, such as diversifying risk, saving mobilization, facilitating transactions, allocating funding to economic activities, and monitoring borrowers’ activities. Based on the GMM estimator, our empirical findings support that better-developed financial markets reduce inequality.